A low-cost smart parking solution for smart cities based on open software and hardware - Serrão, C.; Garrido, N. (Intelligent Transport Systems, From Research and Development to the Market Uptake. Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, 2018)
Traffic management and car parking on modern cities continues to be a problem both for citizens and for city officials. The increasing number of vehicles flowing into the city drain the existing scarce parking resources, and the increase in time spent looking for a parking spot leads to more congestions, parasitic traffic, whilst augmenting fuel consumption and air pollution. In this paper we present an integrated flexible solution developed to help address this issue, using open hardware and software components to develop a low-cost smart parking system suitable for contemporary metropolitan cities. The smart parking solution is based on Arduino boards for the sensors network and on Raspberry Pi single-board computers for the gateway devices, integrated through specific developed software components and a mobile application for the end-users.